(untitled) (Research, Society and Development, 2022)
Burnout syndrome is characterized as a form of occupational stress. The teaching profession represents one of the categories most affected by Burnout Syndrome and several studies have detected the presence of the Syndrome at all levels of education. Research on the profile of the researcher describes the initial training, region of concentration and area of ​​training and elects productivity in the description of these characteristics. Behaviors in relation to the work environment need further investigation. Thus, analyzing the profile of Brazilian researchers in relation to the work environment allows for a more accurate explanation of the way in which their research is produced. The general objective of this study is to identify the profile of Brazilian researchers in relation to work-related stress levels. A validated questionnaire on stress was applied (The validated questionnaire is the O MBI (Maslach Burnout Inventory) prepared by Christina Maslach and Susan Jackson in 1978) to researchers who work in strico-sensu programs in Brazil, chosen at random. 55 researchers responded. The results indicated that emotional exhaustion was the dimension with the highest average. Emotional exhaustion, in Maslach’s theoretical model, is the precursor dimension of the burnout syndrome, demanding preventive attitudes towards stress to avoid chronic diseases arising from this issue and to preserve the quality of life of these professionals.